2022
DOI: 10.3390/cancers14092339
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of NKG2D Stress Ligands and Its Relevance in Cancer Progression

Abstract: Under cellular distress, multiple facets of normal homeostatic signaling are altered or disrupted. In the context of the immune landscape, external and internal stressors normally promote the expression of natural killer group 2 member D (NKG2D) ligands that allow for the targeted recognition and killing of cells by NKG2D receptor-bearing effector populations. The presence or absence of NKG2D ligands can heavily influence disease progression and impact the accessibility of immunotherapy options. In cancer, tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 241 publications
0
15
0
Order By: Relevance
“…In this study, our results suggested that CD122 + NKG2D + bystander-activated CD8 + T cells could produce abundant granzyme B and perforin ( Supplementary Figures 1 , 2 ). Indeed, NKG2D can directly bind to a diverse family of ligands on the surface of target cells, thereby resulting in the activation or synergistic stimulation of immune effectors and subsequently release of cytolytic molecules ( Jones et al., 2022 ). Thus, NKG2D + cells might be positive totally for the expression of granzyme and perforin.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, our results suggested that CD122 + NKG2D + bystander-activated CD8 + T cells could produce abundant granzyme B and perforin ( Supplementary Figures 1 , 2 ). Indeed, NKG2D can directly bind to a diverse family of ligands on the surface of target cells, thereby resulting in the activation or synergistic stimulation of immune effectors and subsequently release of cytolytic molecules ( Jones et al., 2022 ). Thus, NKG2D + cells might be positive totally for the expression of granzyme and perforin.…”
Section: Discussionmentioning
confidence: 99%
“…One approach entails the engagement of ligand families that are commonly dysregulated in cancer, such as the eight NKG2D ligands. These ligands are upregulated by cell stress events such as DNA damage that are highly prevalent in transformed cells 6 . Accordingly, it is estimated that at least 80% of human cancers express these ligands 7–12 .…”
Section: Target Selectionmentioning
confidence: 99%
“…NKG2D (encoded by the killer cell lectin-like receptor subfamily K, member 1, or KLRK1 gene) is a C-type lectin receptor and a major activating immunoreceptor involved in tumor immune surveillance. NKG2D is expressed on the surface of most cytotoxic lymphocytes such as Natural killer (NK) cells, CD8+ T cells, some γδ T cells, and possibly also on some CD4+ T cells and is known as a sensor for damaged or dangerous cells [ 1 , 2 ]. Ligands for NKG2D are generally not expressed on healthy cells but are induced on the surface of malignant cells.…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously described that the transcriptional upregulation of NKG2D-L mainly depends on the activation of cellular stress signals, although the specific molecular mechanisms remain largely unknown. In general, inducible expression of NKG2D-L is observed in response to oncogenic transformation, cell cycle alterations, and DNA damage [ 1 ]. NKG2D-L induction in mice was attributed to a hyperproliferative state which activates the E2F transcription factor and p53, allowing the transcription of NKG2D-L.…”
Section: Introductionmentioning
confidence: 99%